Comparison of Air Puff Tonometer with Gold Standard Applanation Tonometer for Measurement of Intraocular Pressure in Adult Population: Intraocular Pressure Measurement Comparison - Shaikh, Yaruq Sami; Jatoi, Asadullah (Pakistan Journal of Health Sciences, 2024)
Detecting and treating glaucoma early is vital to prevent vision loss. Two main instruments, the Air Puff Tonometer and the Gold Standard Applanation Tonometer, are used to measure Intraocular Pressure (IOP). However, there is ongoing debate among ophthalmologists regarding the accuracy and reliability of these devices. Objective: To evaluate and contrast the measurements of intraocular pressure obtained through Air puff tonometry and Goldmann applanation tonometry. Methods: A cross-sectional comparative study was conducted upon 900 patients of Glaucoma, selected through purposive sampling technique, attending the Eye OPD of Isra University Hospital, Hyderabad. Patients with age more than 18 years, of both genders who provided consent for eye examination and treatment, were included in the study while patients with corneal disease or prior surgery, ocular trauma, or those presenting with active infection or ocular disease were excluded from the study. Results: 396 (44.0%) of patients were males and 504 (56.0%) were females. The results indicate that the mean IOP measurement for air puff tonometry (17.43 mm Hg) is significantly higher (p-value=0.0001) than the mean measurement obtained by Goldman tonometry (13.84 mm Hg). Overall, the distribution of IOP was similar for both types of tonometry, with a slightly higher proportion having high IOP values (19-22 mmHg) with Goldman tonometry compared to air puff tonometry. Conclusions: The findings of this research demonstrated a noteworthy contrast between the two techniques, where the air puff tonometry produced noticeably elevated intraocular pressure measurements in comparison to the widely accepted applanation tonometry